(untitled) (Research Announcements "Heritage BG", 2025)
The study presents the hidden theoretical discourse during the work process on the Tell Yunatsite conservation project1. The article questions some traditional understandings of the conservation of cultural heritage based on a case study of one of the rare prehistoric sites in Bulgaria. What do we conserve here? What is authentic? Is reversibility possible or could we accept the loss? Is it possible to overcome gravity? Could (and should) conservation activities also give meaning of the site to the people? References: Primary sources: Aslan, Zaki. "Protective Structures for the Conservation and Presentation of Archaeological Sites." Journal of Conservation and Museum Studies, 3, 1997, pp. 16–20. Aslan, Zaki, Sarah Court, Jeanne Marie Teutonico, and Jane Thompson. Protective Shelters for Archaeological Sites: proceedings of a symposium (Herculaneum, Italy, 23–27 September 2013). The British School at Rome, 2018. Caple, Chis. Conservation Skills: Judgement, Method, and Decision Making. Routledge, 2000. Cosgrove, Denis. "Should We Take It All So Seriously? Culture, Conservation and Meaning in the Contemporary World." Durability and Change. The Science, Responsibility and Cost of Sustaining Cultural Heritage, edited by W. E. Krumbein, P. Brimblecombe, D. E. Cosgrove, and S. Staniforth, John Wiley, 1994, pp. 259-266. Lowenthal, David. Possessed by the Past. The Heritage Crusade and the Spoils of History. The Free Press, 1996. The Nara Document on Authenticity, ICOMOS.. 1994, www.icomos.org/charters/nara-e.pdf. Oddy, Andrew and Sara Carroll, editors. Reversibility – Does It Exist? British Museum, Occasional paper, Number 135, 1999. Stovel, Herb. "Origins and Influence of the Nara Document on Authenticity." APT Bulletin, vol. 39, no. 2/3, 2008, pp. 9-17. Viñas, Salvador Muños. Contemporary Theory of Conservation. Elsevier Ltd., 2005. Viñas, Salvador Muños. On the Ethics of Cultural Heritage Conservation. Archetype Publications, 2020. Secondary sources: Boyadzhiev, Yavor, and Kamen Boyadzhiev. "Tell Yunatsite – Archaeological Studies and Perspectives." Balkan Heritage Series – Research 2, in press. Katincharov, Merpert, Titov, Macanova, Abilova 1995: Katincharov R.V., Merpert N.Y., Titov V.S., Macanova V.H., Abilova D.I. Selishtna mogila pri selo Yunatsite (Pazardzhishko), Tom I SHSH, Istoriya na prouchvaniyata, Obshta stratigrafiya, Plast A. Agato. Sofia. Boyadzhiev, Yavor, Kamen Boyadzhiev, Lennart Brandtstätter, and Raiko Krauß. "Chronological Modelling of the Chalcolithic Settlement Layers at Tell Yunatsite, Southern Bulgaria." Documenta Praehistorica, vol. 48, 2021, pp. 2–25. Terzijska-Ignatova, Stoilka. "Late Chalcolithic Zoomorphs from Tell Yunatsite." Prehistoric Trace, edited by Vassil Nikolov, Krum Băčvarov, and Peter Kalchev, Stara Zagora, 2004, pp. 383–390.